Synthesis and Characterization of M+Co V2O5 (M+ = Li+, Na+, K+) and Their Electrochemical Impedance Spectroscopic Studies. (2017) - Vaidyanath, Y.N.; Ashamanjari, K.G.; Mylarappa, M.; Ramu, M.S. Bhargava; Mahesh, K.R. Vishnu; Prashanth, S.C.; Nagaswarupa, H.P.; Raghavendra, N.
Abstract: The electrical conductivity of M + CoV2 O5 was investigated as a function of the nature of the transition-metal cation. A series of M + CoV2 O5 (M+= Li +, Na + and K + ) materials have been synthesized by soft hydrothermal technique at moderate pressure and temperature conditions. Observation through a Scanning Electron Microscope shows that microstructures of the resultant materials. The resultant powder X-ray diffraction confirms that, the M + CoV2 O5 (M + = Li +, Na + and K + ) material has very good crystal structure. The EDAX spectrum shows the clear identification of metal composition. The FTIR studies revealed that the presence of O-H molecules and minute structural variations of synthesized materials. Impedance measurement revealed that the materials have relatively good ionic conductance.